FACTORS INFLUENCING THE INCIDENCE OF MENSTRUAL PAIN FOR YOUNG WOMEN IN MADRASAH ALIYAH PALANGKA RAYA CITY - Aida Kusnaningsih (Jurnal Scientia, 2023)
Menstrual pain (dysmenorrhea) is a painful condition experienced by a woman, the influenced of imbalanced levels of the hormone progesterone in the blood. Various factors can influence the incidence of dysmenorrhea. So that the study aims to identify the factors that influence the incidence of dysmenorrhea. The research design used analytical methods and cross-sectional approaches. The sampling technique used consequential on 138 respondents. The instruments used questionnaires and data were analyzed by frequency distribution test, chi-square test and multiple logistic analysis test. The results of this study stated that the variables of menarche age, knowledge, level of depression, level of anxiety, level of stress, physical activity, nutritional status and state of anemia were not significantly associated with the incidence of dysmenorrhea. The variable history of menstrual pain in the family showed a significant relationship with the incidence of dysmenorrhea and adolescents with a history of dysmenorrhea had a 3.94 times chance of experiencing pain. The variable that has the greatest influence on adolescent menstrual pain is a family history of dysmenorrhea.